The radiosensitive effect of apatinib for hepatocellular carcinoma patient with big paraspinal metastasis: A case report. Issue 2 (January 2018) - Zhu, Hong; Zhao, Yaqin; Wang, Xin
Abstract: Rationale: Hepatocellular carcinoma (HCC) is a highly invasive cancer associated with great mortality rates. The prognosis of advanced HCC is very poor. Patient concerns: Here, we report a HCC patient with a big paraspinal metastasis with 10 cm in diameter who failed the treatment of sorafenib. Diagnoses: Sorafenib refractory HCC with big paraspinal metastasis. Interventions: The concurrent treatment of apatinib with stereotactic body radiotherapy (SBRT). Outcomes: The paraspinal metastasis with 10 cm in diameter showed nearly complete response. Lessons: We think that the apatinib may be a good choice for HCC and it may function as a radiosensitizer of HCC. However, it warrants further investigation in the future prospective clinical studies.